2018
DOI: 10.1186/s12935-018-0514-2
|View full text |Cite
|
Sign up to set email alerts
|

Different TP53 mutants in p53 overexpressed epithelial ovarian carcinoma can be associated both with altered and unaltered glycolytic and apoptotic profiles

Abstract: Backgroundp53 is a tumor suppressor and key regulator of glycolysis in cancer cells, however highly mutated in tumors. In ovarian cancer, studies concerning p53 mutations focus on the DNA binding domain since the majority of hotspot mutations affects this region. Yet, mutations in other regions such as the proline rich domain may also affect the protein’s expression and activity. The aim of this study is to investigate the effect of various positions of mutations in TP53 gene on glycolysis, apoptosis and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…p53 is an important target protein for SIRT1.Previous study indicated that the selective SIRT1 inhibitor, EX527, significantly suppressed the proliferation of endometrial carcinoma cells regardless of the p53 mutation status [52,53]. Thus, activation of the p53 pathway through SIRT1 inhibition has been shown to have powerful anticancer effects [54]. Our present data indicate that activation of the apoptosis-related signal pathway via up-regulation of p53, plays a pivotal role in MHY2245-induced cell death.…”
Section: Discussionsupporting
confidence: 51%
“…p53 is an important target protein for SIRT1.Previous study indicated that the selective SIRT1 inhibitor, EX527, significantly suppressed the proliferation of endometrial carcinoma cells regardless of the p53 mutation status [52,53]. Thus, activation of the p53 pathway through SIRT1 inhibition has been shown to have powerful anticancer effects [54]. Our present data indicate that activation of the apoptosis-related signal pathway via up-regulation of p53, plays a pivotal role in MHY2245-induced cell death.…”
Section: Discussionsupporting
confidence: 51%
“…However, one particular mutation p53P72R showed increased PGC1α function and increased metastatic capability [ 191 ]. Even though this mutation didn't show evidence of increased glucose regulation compared to wild-type p53 [ 192 ].…”
Section: Regulation Of Metabolism By P53mentioning
confidence: 99%
“…e P72R polymorphism is present in the segment encoding the transactivation domain and may increase the expression of this gene and the levels of anti-TP53 antibodies [28].…”
Section: Discussionmentioning
confidence: 99%